Effective Village Fund Utilization Model In Alor Regency, East Nusa Tenggara - Edy Sutrisno; Aristarkus Mabileti (Yayasan Ilomata, 2023)
Through a descriptive method with a qualitative approach, this study discusses an effective village fund utilization model in Alor Regency, East Nusa Tenggara. The results showed that the use of village funds from 2015-2018 based on priorities for benefit, community participation, sustainability, certainty of supervision, village resources, and typology in six villages in East Nusa Tenggara with certain categories could be said to be ineffective, seen from the village fund realization document which shows that the majority of village funds are used for the field of infrastructure development compared to the field of community empowerment. Keywords : Village Funds, Village Development, Community Empowerment